2020
DOI: 10.1037/fsh0000529
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience with a large-scale integrated behavioral health and primary care initiative: A qualitative study.

Abstract: Introduction:Patient engagement in research can improve a health system's responsiveness to patient need, but patient experience with integrated care is not well understood. This qualitative study explores patient experience and provider perceptions of patient experience with the Behavioral Health Integration and Complex Care Initiative (BHICCI), which is a large-scale system redesign that delivers integrated care to persons with complex needs. Methods: We conducted 8 patient focus groups (n ϭ 54 patients) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This review supports the positive impact of care coordination on patients’ experience and found that patients considered PREMs a critical feedback tool to assess and improve the quality of care across various clinical settings and between staff within a healthcare team [ 24 , 32 ]. Arguably, for some health conditions such as chronic wounds, disease specific PREMs may be useful to assess condition-specific aspects of care coordination, interdisciplinary communication, and shared decision-making [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…This review supports the positive impact of care coordination on patients’ experience and found that patients considered PREMs a critical feedback tool to assess and improve the quality of care across various clinical settings and between staff within a healthcare team [ 24 , 32 ]. Arguably, for some health conditions such as chronic wounds, disease specific PREMs may be useful to assess condition-specific aspects of care coordination, interdisciplinary communication, and shared decision-making [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 54%
“…Table 1 provides a summary of the 20 included studies. Five studies (25%) were conducted in primary care settings [ 4 , 21 – 24 ], nine (45%) in hospitals [ 8 , 25 32 ], and the rest either in psychological therapy services [ 33 ], a disability care organization [ 34 ] or other healthcare settings such as Veterans Health Administration [ 35 ] or National Health Service (NHS) [ 36 ]. Studies were conducted in the UK (N = 9; 45%), the USA (N = 8; 40%), Ireland (N = 1; 5%), Brazil (N = 1; 5%) and the Netherlands (N = 1; 5%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insights from patients can highlight intrinsically valuable and meaningful aspects of health care related to patient experience, enabling a better understanding of current problems with health care delivery, pushing continuous improvement, redesigning the delivery of services and helping professionals reflect on practice. Therefore, qualitative researches have been widely used to explore patient experience with health care services (Davis et al., 2018; Siantz et al., 2020). In October 2011, the English National Health Service (NHS) published patient experience framework, outlining 8 elements that were critical to the patient experience of NHS Service: (i) respect for patient‐centred values, preferences and expressed needs; (ii) coordination and integration of care; (iii) information, communication and education; (iv) physical comfort; (v) emotional support; (vi) welcoming the involvement of family and friends; (vii) transition and continuity; and (viii) access to care (Department of Health, 2011).…”
Section: Introductionmentioning
confidence: 99%